Personal Data Protection in Review of Legal Theories and Principles - Supeno, Supeno; Rosmidah, Rosmidah; Iqbal, Syed Mohd Uzair (Universitas Negeri Semarang, 2025)
The abuse of personal data for certain interests and causing harm to other parties is often occur so that this raises concerns as a large community in conducting online transactions, in 2022 the President together with the Indonesian Parliament has enacted Law Number 27 of 2022 on Personal Data Protection (PDP) which aims to provide legal protection for the community against their personal data, this provides good hope to ward off various kinds of acts of misuse of personal data, the purpose of this study is to reveal the legal protection of customer data in online transactions after the legalization of personal data protection law seen from legal theory and how the personal data dispute resolution model is in line with the ultimum remidium principle. The type of research used is juridical-normative law using normative and theoretical approaches. The results showed that the protection of one’s privacy rights in online transactions is an embodiment of absolute right theory because the protection of privacy rights is a basic right that everyone must respect, the utilization of one’s privacy rights without the approval of the right owner is a violation of the law, the personal data dispute resolution model in the personal data protection law is not in following with the ultimum remidium principle, the personal data dispute by special organ with like such as the General Data Protection Regulation (GDPR) in the European Union, because it can resolve cross-border personal data cases.